The novel roles of DNA damage repair proteins ATM and DNA-PK in the regulation of the ER stress response and IL-23 expression in dendritic cells - Shah, Sabaria (2017)
Dendritic cells (DC) are the principal, cross-priming antigen-presenting cell responsible for naïve T cell activation and differentiation. Specific programmes of cytokine secretion by DC are particularly important for the polarisation of CD4+ T-cells to discrete effector populations i.e. Th1, Th17, Tr1 etc. Our knowledge of control for some of these cytokine signals is currently limited and modulating the polarisation of defined Th-subsets remains a challenge. Improved control of Th-differentiation has considerable potential in the fields of immune disorders and infectious disease. We describe a novel immune-regulatory function of two DNA-repair proteins signal to modulate IL-23 secretion, a key signal for Th17 differentiation.